Research Progress of Chinese Medicine Against Tumor Angiogenesis - Gou, Tao; Zhang, Yucun (Journal of Contemporary Medical Practice, 2024)
With the continuous development of the society, people's life style and living environment changing, malignant tumor disease from the past rare disease rare disease gradually tends to the high incidence of common disease change, according to incomplete statistics, in 2020, the global 12. 7 million people with new tumors, death 7. 6 million people, with an annual average of 3% to 5% increment, of which 56% of new cases and deaths come from developing countries. In China, the number of new cases of malignant tumors in 2020 will be about 3. 929 million, and the incidence rate of malignant tumors in the country will be 285. 83/100, 000, and the overall situation of prevention and control of malignant tumors is becoming more and more serious. The overall situation of prevention and control of malignant tumors is becoming more and more serious. At the same time, as the occurrence and development process of malignant tumor disease, the key link of tumor angiogenesis, which is decisive, has become an important research direction to inhibit the growth of tumor cells recurrence and metastasis. In recent years, seeking effective anti-tumor angiogenesis components and treatments from traditional Chinese medicine is a hot spot for the treatment of inhibition of the continuous deterioration of malignant tumors. Especially, the effective components of herbal extracts showed strong tumor neovascularization inhibition.